Care as resistance on behalf of the commons: Feminist political ecologies and anti-extractivism in Covas do Barroso, Portugal - Leonardo, H. de S. C.; Esteves, A. M.; Disterheft, A. (Capitalism Nature Socialism, 2025)
This article investigates the anti-lithium mining resistance in Covas do Barroso, Portugal, through the frameworks of feminist political ecology and care ethics. As lithium becomes central to Europe’s green energy agenda, the proposed mine in Barroso threatens not only local ecosystems and livelihoods but also the communal lifeways that define the region. Drawing on ethnographic fieldwork and interviews (n = 15), the study explores how care is mobilized as a political practice that resists extractivism while sustaining community. Rather than viewing care as an apolitical or individualized practice, the thematic analysis foregrounds the role of care in shaping collective governance, emotional resilience, artistic expression, and solidarity networks. The resistance, organized under the association Unidos em Defesa do Barroso [United in the Defense of Barroso], embodies an alternative vision of sustainability rooted in reciprocity, self-determination, and ecological stewardship. Findings suggest that care functions as both the fabric and force of resistance, enabling communities not only to endure environmental and political pressures but to cultivate alternative modes of development that challenge dominant growth logics. The Barroso case thus contributes to broader conversations on degrowth, environmental justice, and post-extractivist futures, revealing care as a vital, generative force in the struggle for climate and social justice.